Development of the Talent Identification Questionnaire in Soccer for Outfield Players (TIDQ-OP): Coaches` perceptions of the key attributes for player recruitment - Lethole, L.; Kubayi, A.; Toriola, A.; Larkin, P.; Armatas, V. (Journal of Sports Sciences, 2024)
Talent identification in sports is a complex process, whereby the aim is to identify, select and promote players who are considered to have the necessary skills and competencies (e.g., technical, tactical, and physical attributes) to succeed in senior adult competition. To support this process, this study focused on the development of a questionnaire to assist in the identification of talent among South African youth soccer players. This will establish a measure of the attributes coaches consider important when making talent identification decisions for outfield soccer players. The questionnaire was constructed following established instrument development phases. In phase 1, 61 questionnaire items were generated based on a review of the relevant literature. In phase 2, a panel of experts examined the content validity of the preliminary items. In phase 3, the provisional 59-item questionnaire (Talent Identification Questionnaire in Soccer for Outfield Players; TIDQ-OP) was administered to 173 experienced South African soccer coaches (130 males and 43 females) who ranged in age from 18 to 64 years. In phase 3, the factorial structure of the questionnaire was established through principal component analysis. The final questionnaire consisted of 58 items. These preliminary analyses indicate the usefulness of the TIDQ-OP as a tool to assist South African coaches in the identification and selection of talented players.